Older adult care management: opportunities and challenges in the field of Gerontology - Salmazo-Silva, Henrique (2013)
The aim of this article was to present a critical reflection on the literature about elderly care management, discussing the possibilities and challenges for brazilian Gerontology. The management concept in Gerontology proposes that a set of proactive actions associated with the prevention and promotion of active aging can maximize old person independence, autonomy and well-being as well as the old person family and their community. In order to implemented this actions one must strengthen primary health care systems, integrate social and health care, optimize resources and information technologies, and train professionals to develope an understanding about aging as a dynamic and complex phenomenon which needs social responses in short, medium and long term.